Evolutionary priority effects in New Zealand alpine plants across environmental gradients. (21st November 2014) - Leopold, Devin R.; Tanentzap, Andrew J.; Lee, William G.; Heenan, Peter B.; Fukami, Tadashi; Richardson, James
Abstract Aim Priority effects, in which the order and timing of species arrival influence community assembly, are thought to be stronger in less stressful environments, reflecting increased competition, but this hypothesis has rarely been examined over evolutionary time. Here, we test the hypothesis using an island community of alpine plants. Location Murchison Mountains, South Island, New Zealand. Methods Lineage age data for 14 monophyletic New Zealand alpine plant genera, with stem ages ranging from 2 to 17 Ma, were paired with species presence and abundance data in 261 plots, covering nearly 400 km2. The relationships between lineage age and the relative abundance and richness of focal genera across elevation (800–1620 m) and precipitation (2500–5000 mm yr−1) gradients were investigated using linear models in a Bayesian framework. Results The relative abundance of focal genera increased with lineage age, but this effect was weaker at higher elevation and precipitation, where plants are likely to have experienced more stressful conditions. The relative richness of focal genera increased at a consistent rate despite significant changes in overall richness of focal genera across both elevation and precipitation gradients. Main conclusions Our results suggest that priority effects, on a time‐scale of millions of years and involving significant evolutionary change, influence community assembly, leading to increased dominance of older lineages, but that the strength of these effects may vary with environmental conditions. Environmental gradients correlated with abiotic stress, such as elevation in alpine systems, may be particularly important for predicting the strength of both ecological and evolutionary priority effects.